Reproductive outcome of hysteroscopic metroplasty for women with T-shaped uterus: a retrospective study - Yuxin Zhang; Yiping Zhu; Beilei Ge; Mengsong Sui; Zhenzhen Zheng; Jing Sun (BMC, 2022)
Plain language summary As a Müllerian malformation, T-shaped uterus is named for the shape of the uterine cavity. According to cause of the disease and patients' intrauterine operation history, T-shaped uterus can be divided into congenital and acquired types. This study was conducted in the reproductive surgery unit in a university-affiliated hospital. Data were collected from medical records, and patients were followed up via telephone. One hundred and eleven patients were included in this study, with 46 in congenital group and 65 in acquired group. Whether infertility/subfertility patients had had intrauterine operation history or not, their rates of giving live birth increased after the hysteroscopic metroplasty. In conclusion, hysteroscopic metroplasty is an effective intervention for T-shaped uterus patients with fertility intention.